Pengembangan Modul Sistematika Cryptogamae: Keanekaragaman Jenis Rumput Laut Di Dusun Labuhan Terata - Mursali, Saidil; Saputra, Erwin; Safnowandi, Safnowandi (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2024)
This study aims to develop a Sistematika Cryptogamae module based on research findings on the diversity of seaweed species in the waters of Dusun Labuhan Terata, Sumbawa Regency, West Nusa Tenggara. The research was conducted using a development method that refers to the ADDIE Model by Reiser and Mollenda, which includes Analysis, Design, Development, Implementation, and Evaluation. This study is limited to the Development stage. The research instruments are validation sheets and readability questionnaires. Data analysis is conducted using a descriptive quantitative approach. The validity test results of the Sistematika Cryptogamae module reached 86.6%, categorized as highly feasible. In addition, the readability test results reached 84.4%, categorized as easy to understand. This module was developed using a research-based approach and local environmental context to meet the needs of contextual education. It is expected to enhance students' understanding of the diversity of lower-level plants, particularly seaweed, and to foster awareness of marine ecosystem conservation. This research also contributes to the documentation of biodiversity and the sustainable management of seaweed resources. The conclusion of this study is that the Cryptogamae Systematics module developed is deemed highly suitable for implementation in learning.